Investigating The Adoption of Augmented Reality for Vocational Student Engineering Materials in Hybrid Learning - Badriyah, Nurul Lailatul; Yusuf, Munawir; Efendi, Agus (Journal of International Conference Proceedings, 2023)
Education in Indonesia has experienced developments related to the use of technology. Learning on personal computers (PC) and smartphone technology devices is common, and it is also referred to as "hybrid learning." However, when researchers conducted a survey of SMK students in Surakarta, even though they had used personal computers or gadgets, they only used a few media software programs to study engineering material. Seeing this phenomenon, researchers want to identify students' needs for media software, namely mobile augmented reality. This identification aims to provide a critical initial analysis of the need for mobile augmented reality learning media software that is connected to a smartphone for engineering learning for SMK students. The research samples involved were students of SMK N 2 Surakarta and SMK N 5 Surakarta. Using questionnaires, field observations, and interviews as data collection techniques. The data obtained were analyzed descriptively. Define part of the 4D research model using the research method, and the research results show that SMK students in Surakarta require mobile augmented reality media in learning engineering material if hybrid learning is used.